Islamic Financial Reporting: A Bibliometric Network Analysis of Research Frontiers (2000–2026) - Loso Judijanto (Westscience Press, 2026)
This study aims to map the intellectual structure, thematic evolution, and emerging research frontiers of Islamic financial reporting through a comprehensive bibliometric network analysis. Using data extracted from the Scopus database covering the period 2000–2026, the study applies VOSviewer to analyze co-authorship, co-citation, and keyword co-occurrence networks. The findings reveal that the literature is primarily concentrated around core themes such as Islamic banks, financial reporting, corporate governance, AAOIFI, and IFRS, indicating a strong focus on regulatory frameworks and institutional practices. The results also identify several major research clusters, including governance and reporting quality, disclosure and accountability, and standardization of Islamic accounting practices. Temporal analysis shows a clear shift from early conceptual and normative discussions toward more empirical and context-driven studies, particularly in regions such as Southeast Asia and the Middle East. More recent developments highlight the growing importance of sustainability reporting, risk management, sukuk, and IFRS 9, suggesting a convergence between Islamic financial reporting and global trends in ESG and responsible finance. Despite the maturity of the core literature, density analysis indicates that emerging themes remain underexplored, offering significant opportunities for future research. This study contributes to the literature by providing a systematic and visualized understanding of the development of Islamic financial reporting and by identifying key directions for future scholarly inquiry.